SOCIALIZATION OF AVOCADO USE TO ADDRESS CHRONIC ENERGY DEFICIENCY (CED) AMONG WOMEN OF REPRODUCTIVE AGE IN TELADAN VILLAGE, SUB-DISTRICT SEULAWAH, THE DISTRICT OF ACEH BESAR - Berkat, Satrinawati; Fithriany, Fithriany; Juliastuti, Juliastuti; Putri, Isnaini; Ritawati, Ritawati (Journal of Midwifery and Community Health (JMCH), 2025)
Chronic energy deficiency (KEK) in pregnant women is a long-standing lack of energy intake. This is characterized by the mother's upper arm circumference (LILA) ≤ 23.5 cm. Pregnant women with KEK are at risk of weakening the muscles that assist in the birthing process, leading to prolonged labor, postpartum bleeding, and even maternal mortality. The prevalence of KEK among pregnant women in Indonesia in 2018 was 17.3%, and KEK in Aceh was 11.27%. Generally, pregnant women with KEK also suffer from anemia. The indicator of anemia in pregnant women is if hemoglobin < 11 g%. The health condition of pregnant women and their fetuses will worsen if the mother suffers from KEK and anemia. Avocado is one of the local food alternatives to address KEK and anemia in pregnant women.The purpose of this activity is to increase public awareness of the impact of KEK during pregnancy on the health of the mother and fetus, the benefits of avocado for the health of pregnant women, change public attitudes towards the utilization of avocado for the health of pregnant women and change the behavior of the public to consume avocado regularly, especially during pregnancy. The methods used were FGD, lectures, demonstrations, and anthropometric and hemoglobin examinations. The activity was conducted on May 29, 2024, from 08:30 to 13:00 WIB. It was attended by midwives in the village, integrated health post cadres, pregnant women, and women of reproductive age (WUS). The participants were 48. The activity ran smoothly and according to plan.